Development of Nursing Practice Guidelines for the Prevention of Pressure Ulcers in the Male Inpatient Ward at Chokchai Hospital, Nakhon Ratchasima Province.: การพัฒนาแนวปฏิบัติการพยาบาลเพื่อป้องกันการเกิดแผลกดทับในหอผู้ป่วยในชายโรงพยาบาลโชคชัย จังหวัดนครราชสีมา - Siriwong, Pornsuda (Journal of Nursing and Health Sciences Nakhon Phanom University, 2024)
This research and development study aimed to develop guidelines for pressure ulcer prevention in the male inpatient ward of Chokchai Hospital, Nakhon Ratchasima Province. The sample consisted of 16 professional nurses working in the male inpatient ward and 19 patients admitted to the male inpatient ward of Chokchai Hospital with Braden score > 16 points. The purposive sampling was used. The study was conducted from June 2024 to July 2024. The research instruments were a questionnaire consisting of 4 sets of data: 1) Personal information of patients, 2) Personal information of professional nurses, 3) Pressure ulcer prevention practice compliance measurement form, and 4) Nurse satisfaction measurement form. The research results found that professional nurses followed the guidelines for pressure sore prevention at 52.25 percent and 100 percent correctly followed 3 items: assessment of skin condition of the initial wound, lifting and moving, changing patient positions by more than 2 people, lifting patients off the floor, and providing knowledge on pressure sore prevention. The results of using the guidelines for pressure sore prevention found that 2 patients had pressure sores at initial admission, 1 patient had improved pressure sores, and 17 patients did not have pressure sores. The satisfaction of professional nurses with using the guidelines for pressure sore prevention in the male inpatient ward of Chokchai Hospital was at a very satisfactory level. Recommendations: There should be an announcement of policies, key performance indicators should be set in relevant agencies, there should be clinical supervision, and there should be monitoring and evaluation of performance to promote continuous practice.